The rise of the sound designer: Northern California film sound in the 1960s and 1970s - Andriano-Moore, Stephen (Taylor & Francis, 2017)
Northern California based filmmakers in the late 1960s and 1970s pushed the traditional boundaries of filmmaking practices in ways that have been adopted and reworked into contemporary Hollywood filmmaking practices. The article examines labour issues and conditions and politics of film sound work during this era, some of which continue to be applicable today. The development of new production practices pushed filmmakers including George Lucas, Francis Ford Coppola, and Walter Murch to produce films outside the traditional Hollywood studio production paradigm. This new generation of filmmakers held sound with a higher status and popularized non- traditional ways of working with sound. They created the new job title of sound designer to signify a person who supervises and collaborates with the director, department heads, and screenwriter on the use and function of sound through all of the filmmaking phases from the writing stage through the final mix. Through this historical view of the issues, conditions, and politics of Hollywood film sound labour as experienced by practitioners at the early period of the contemporary film sound era, this article illuminates the reasons and ways in which filmmakers sought to work outside of studio controls and union regulations that inhibited their emerging production processes, and led to formation of a media capital for film sound in the San Francisco Bay Area.